Analysis of national examination council junior school certificate examination question in two core subject. (2010)
The study is an anlaysis of context coverage of Junior School Certificate Examination Syllabi by National Examination Council Papers in two core Subject. The extent to which itema on the test present Blooms Taxonomy of Educational Objectives (cognitive domain) was also analysed. The ex-post-factor research design was adopted in the study. Examination syllabi for Social Studies and integrated science and question papers for a three year period were collected and analysed using descriptive statistics. Findings indictated that NECO JSCE Integrated Science and Social Studies questions cover between 50% and 60% of the examination syllabi. Most of the areas not adequately covered were very relevant to everyday life. Generally, Social Studies multiple choice items were easy but in 2001 and 2003 the essay items were difficult as 33% and 40% were at the application level respectively. Integrated science multiple choice questions and essay question for 2004 were difficult as they covered 30% and 46% application level respectively. In view of the findings, it was suggested that to meet the standard of NECO questions, the subject teachers should develop in students the skills and strategies for answering higher order questions to keep pace with the changing patterns of questions presentation.